A study of the urban poetics of Frank O'Hara - Wang, Xiaoling, 1971-; Wang, Yuzhi, 1962-; Zheng, Mingyuan, 1980- (Abingdon, Oxon ; New York, NY : Routledge, 2022)
"Focusing on the poetry and cultural practice of Frank O'Hara, the great urban poet in the New York School during the 1950s and 1960s, the title explores the interwoven relationship between his urban poetics and the urban culture of New York, seeking to shed light on the poetic concept and its cultural relevance. The poetry writing of Frank O'Hara is deeply rooted in and nourished by his urban experience as a metropolitan and an active participant in the vibrant cultural scene in New York. Therefore, an investigation on the interactive dynamics between his poetry writing and the urban culture he helped shape offers a feasible approach to his urban poetics, which serves as a starting point for further study on the literary representation of European and American urban culture. In the eight chapters, the authors look into the genesis, theoretical constitution, interface with culture and aesthetics of O'Hara's urban poetics and also the philosophical foundation, literary ethics, special expression and representation as well as the reception of modernity and postmodernity in his poetics. The title will appeal to scholar, students and general readers interested in American literature, poetry and urban culture, especially Frank O'Hara and the New York School"--
The origin of Frank O'Hara's urban poetics -- Theoretical basis of Frank O'Hara's urban poetics -- The culture of Frank O'Hara's urban poetics -- The aesthetics of Frank O'Hara's urban poetics -- Philosophy in Frank O'Hara's urban poetics -- Literary ethics in Frank O'Hara's urban poetics -- Space in Frank O'Hara's urban poetics -- Modernity, postmodernity and last words.
"This book project is partially sponsored by Shanghai Pujiang Scholars Fund."
Translation of: Fu lan keAo ha la cheng shi shi xue yan jiu.
Keywords: O'Hara, Frank, -- 1926-1966 -- Criticism and interpretation; City and town life in literature; American poetry -- 20th century -- History and criticism; Poets, American -- 20th century -- Biography; New York (N.Y.) -- In literature; POETRY / General; POETRY / American; POETRY / English, Irish, Scottish, Welsh